Tax avoidance, tax management and corporate social responsibility - Huseynov, Fariz; Klamm, Bonnie K. (Journal of Corporate Finance, 2012)
This study examines the effect of three measures of corporate social responsibility (CSR) — corporate governance, community and diversity on tax avoidance in firms that use auditor‐provided tax services. This is one of the first studies, to our knowledge, to empirically relate tax avoidance, tax management and CSR literature. By separating the strengths and concerns for each CSR measure, we are able to analyze the effects of a firm's negative and positive social actions on tax avoidance. We find that the interaction of community concerns with tax management fees positively affects both GAAP and Cash ETR, while the interaction of corporate governance strengths and diversity concerns with tax management fees negatively affects Cash ETR. Our results are similar when we use Excess ETR that is not explained by firm specifics. We find additional evidence that CSR affects tax avoidance when we divide firms into portfolios based on CSR levels. Our findings suggest that future studies on tax avoidance and tax management should incorporate CSR.